Conspicuous plumage colours are highly variable - Delhey, Kaspar (Proc Biol Sci, 2017)
Elaborate ornamental traits are often under directional selection for greater elaboration, which in theory should deplete underlying genetic variation. Despite this, many ornamental traits appear to remain highly variable and how this essential variation is maintained is a key question in evolutionary biology. One way to address this question is to compare differences in intraspecific variability across different types of traits to determine whether high levels of variation are associated with specific trait characteristics. Here we assess intraspecific variation in more than 100 plumage colours across 55 bird species to test whether colour variability is linked to their level of elaboration (indicated by degree of sexual dichromatism and conspicuousness) or their condition dependence (indicated by mechanism of colour production). Conspicuous colours had the highest levels of variation and conspicuousness was the strongest predictor of variability, with high explanatory power. After accounting for this, there were no significant effects of sexual dichromatism or mechanisms of colour production. Conspicuous colours may entail higher production costs or may be more sensitive to disruptions during production. Alternatively, high variability could also be related to increased perceptual difficulties inherent to discriminating highly elaborate colours. Such psychophysical effects may constrain the exaggeration of animal colours.